Weeding with Wisdom: Tuning Deselection of Print Monographs in Book-Reliant Disciplines. Issue 2 (3rd April 2017) - McAllister, Alex D.; Scherlen, Allan
ABSTRACT: As university libraries transition to digital collections and new services, their book deselection projects often lead to the adoption of cross-discipline quantitative weeding criteria (such as age and low circulation) in the interest of speed and presumed fairness. Cross-discipline quantitative rubrics, however, can have unintended negative consequences when applied to disciplines such as history and literature that rely on older books with low circulation statistics. The authors argue for a discipline-differentiated approach to weeding academic library collections that can employ quantitative criteria for disciplines, such as in the sciences, that are more reliant on current materials and qualitative criteria for disciplines, such as in the humanities, whose scholars benefit from ready access to older and low-use books.